EFFECT OF PERFORMANCE ASSESSMENT AND COMPENSATION ON EMPLOYEE PRODUCTIVITY (STUDY IN PT. TELEKOMUNIKASI INDONESIA, TBK WITEL JATIM SELATAN MALANG - Wijaya, Adhitya Andri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the effect of the performance assessment and the compensation on productivity in PT. Telekomunikasi Indonesia, Tbk Witel Jatim Selatan Malang. The type of this research is explanatory research which explains the causal relationship between the variables through hypothesis testing. This study used a sample of 57 respondents drawn from some employees in PT. Telekomunikasi Indonesia, Tbk Witel Jatim Selatan Malang. Methods of data collection in this study using a questionnaire that measured with Likert scale, test equipment used to test the research instruments such as validity, reliability, and classical assumption. Data analysis techniques in this research is multiple regression. From the test results it was found that the performance assessmet and variable compensation has an effect on employee productivity. In this study gives the results of their significant influence simultaneously on the performance assessment system and compensation programs on employee productivity. This research concluded: (1) performance appraisal is partially significant effect on the productivity of employees, (2) compensation is partially significant effect on employee productivity. It shows the performance appraisal and compensation affect the productivity of employees at PT. Telekomunikasi Indonesia, Tbk Witel Jatim Selatan Malang.Keywords: Performance Assessment, Compensation, Employee Productivity